The impact of ERα action on muscle metabolism and insulin sensitivity - Strong enough for a man, made for a woman - Andrea L. Hevener; Zhenqi Zhou; Timothy M. Moore; Brian G. Drew; Vicent Ribas (Elsevier, 2018)
Background: The incidence of chronic disease is elevated in women after menopause. Natural variation in muscle expression of the estrogen receptor (ER)α is inversely associated with plasma insulin and adiposity. Moreover, reduced muscle ERα expression levels are observed in women and animals presenting clinical features of the metabolic syndrome (MetSyn). Considering that metabolic dysfunction impacts nearly a quarter of the U.S. adult population and elevates chronic disease risk including type 2 diabetes, heart disease, and certain cancers, treatment strategies to combat metabolic dysfunction and associated pathologies are desperately needed. Scope of the review: This review will provide evidence supporting a critical and protective role for skeletal muscle ERα in the regulation of metabolic homeostasis and insulin sensitivity, and propose novel ERα targets involved in the maintenance of metabolic health. Major conclusions: Studies identifying ERα-regulated pathways essential for disease prevention will lay the important foundation for the rational design of novel therapeutics to improve the metabolic health of women while limiting secondary complications that have plagued traditional hormone replacement interventions. Keywords: Estrogen action, Estrogen receptors, Insulin sensitivity, Metabolic homeostasis